Transport dynamics of sediment‐laden jet: A review. Issue 2 (5th December 2022) - Chen, Yongping; Otoo, Ebenezer; Chen, Yuhang; Xu, Zhenshan; Li, Xingfei; Zhou, Yan
Abstract: Wastewater disposal through the dumping of spoil and sludge into the river, lake, or ocean is typically in the form of a sediment‐laden jet. The inorganic and organic solids from the effluent settling close to the source often result in the formation of sludge banks which can have a damaging effect on the marine ecosystem. Therefore, predicting the transport and deposition of sediment‐laden wastewater jet flows has been a focus of intense research for decades. In this paper, we discussed the fundamental understanding of sediment‐laden jets and the progress made in their predictions. We also highlighted some of the pertinent research challenges revealed by the previous studies and identified some key research issues that need to be addressed to achieve sustainable marine wastewater disposal in the face of increasing river, lake, and marine pollution.